Assessment of nurses' competence to care for sexually assaulted trans persons: a survey of Ontario's Sexual Assault/Domestic Violence Treatment Centres. Issue 5 (27th May 2019) - Du Mont, Janice; Kosa, Sarah Daisy; Solomon, Shirley; Macdonald, Sheila
Abstract : Objective: Our primary objective was to examine the perceived level of competence and need for additional training among nurses engaged in the care of sexually assaulted trans persons. Among these nurses, a secondary objective was to examine the impact of prior trans-specific training on their perceived level of competence. Setting: An online survey was distributed to nurses working within 35 hospital-based violence treatment centres in Ontario, Canada. Respondents: 95 nurses completed the survey. Primary and secondary outcome measures: The perceived level of competence and need for additional training overall and on 31 specific items associated with initial assessment, medical care, forensic examination and discharge and referral, as well as sociodemographic, work experience and prior training information, was collected and summarised using descriptive and inferential statistics. Results: Almost three-quarters (73.1%) of nurses indicated that they had little or no expertise in caring for trans clients who have been sexually assaulted and 95.7% strongly agreed/agreed that they would benefit from (additional) training. The mean level of competence was 4.00 or greater (strongly agreed/agreed with the statement) for just 9 out of the 31 competencies related to caring for trans clients. Having undergone prior trans-specific training (61.3%) was associated with greater perceived competence in initial assessment (p=0.004) and medical care (p<0.001). Conclusion: It is of key importance that nurses demonstrate knowledge of and respond competently to the complex and diverse needs of trans survivors of sexual assault. The nurses surveyed overwhelmingly identified a need for additional training to care for sexually assaulted trans clients. It appears that additional training would be beneficial, as prior trans-specific training was associated with higher perceived competence in delivering certain aspects of care.